An experimental analysis of the spraying processes in improved design of effervescent atomizer. (June 2018) - Zaremba, Matouš; Kozák, Jiří; Malý, Milan; Weiß, Lukas; Rudolf, Pavel; Jedelský, Jan; Jícha, Miroslav
Highlights: New concept of the effervescent atomizer is tested at low operating pressures and consumption. The atomizer is capable to generate relatively stable spray comparing the standard effervescent construction of the nozzle. This is due to the specific breakup mechanism and mixing process inside the atomizer. A breakup mechanism based on the effervescent atomization is examined in detail using high speed imaging, phase Doppler anemometry and several post-processing techniques which enables to describe the whole spray. New features of the effervescent atomization were found and the main aspects of the breakup mechanism were determined using proper orthogonal decomposition and frequency analysis of the high-speed records. Abstract: The present study was experimentally examines the primary atomization processes in a newly developed atomizer, similar to effervescent atomizer concept, at low pressures and low gas-to-liquid ratios (GLR). Several experimental and post-processing techniques are applied to investigate the spray spatial evolution. The near-nozzle area is captured by a high-speed camera with a long-distance microscope. Further, characteristics of the developed spray are investigated by a phase-Doppler analyser (PDA). The high-speed recordings are processed by the proper orthogonal decomposition (POD). The frequency analysis of examined phenomenon is done by the fast Fourier transformation (FFT) at selected positions in the images. The POD enables to sort out data according to the importance of characteristic shapes occurring in the recordings. The velocity and dimensions of discharging liquid are measured in images by a point-tracking method. Dimensionless criteria are estimated to describe the atomization principles where several new findings are found comparing the previous studies. The spatial spray evolution is described by the processed PDA data. A simplification, based on the Stokes number, is used to estimate a gas motion in the spray. This approach enables to investigate the interaction between the spray and ambient atmosphere. The combination of experimental and post-processing techniques confirms the previous findings of the improved effervescent atomizer. In other words, the atomizer operates inherently in annular two-phase flow regime which, however, leads to a specific atomizing mechanism, i.e. bubble bursts, the same as in the effervescent spraying process. However, an importance of the interaction between the two following bubble bursts is highlighted as driving atomization mechanism. This specific behaviour is the reason why the atomizer can be operated at low consumption of gas and low-pressure regimes. Moreover, the applied experimental and post-processing techniques indicate a potential for further advanced data post-processing of the stochastic processes of liquid atomization.